KAJIAN KANDUNGAN FENOLAT DAN AKTIVITAS ANTIOKSIDAN EKSTRAK ETANOL TEMPE GEMBUS DARI BERBAGAI WAKTU INKUBASI - Mohammad Sidiq; Mappiratu Mappiratu; Nurhaeni Nurhaeni (KOVALEN: Jurnal Riset Kimia, 2016)
The research about study of content phenolic and antioxidant activity extract ethanol tempeh gembus of a variety of incubation has been done. This study aims to know the time of incubation and time extraction that produced levels of the total phenolic and the best antioxidant activity. Determination of total phenolic using the method of folin-ciocalteu and antioxidant activity using the method DPPH. The achievement of goals be done through the application of the treatment of the time of incubation and time extraction of level of phenolic and antioxidant activity. The influence of the time of incubation is applied five levels of 0 hours; 12 hours; 24 hours; 36 hours and 48 hours. While the influence of time extraction is 1 hours, 1.5 hours, 2 hours, 2.5 hours, and 3 hours. From the result obtained by the incubation is at the time of incubation 36 hours which resulted in levels of total phenolic of 7.75 % and the value of IC50 0f 1098.88 µg/mL. The use of time extraction is 1,5 hours that produces levels of total phenolic of 5.26 % and the value of IC50 of 1198.95 µg/mL.Keyword: tempeh gembus, total phenolic, antioxidant activity, time of incubation, time extraction